Cape Verde : Public Sector Reform and Capacity Building - Mohan, P.C. (World Bank, Washington, DC, 2012)
Cape Verde was the first single party state to hold pluralistic elections in the African subcontinent in 1991. This process provided extraordinary momentum for reforms. The principal objective of the Public Sector Reform and Capacity building project was to support the government's broader program to transform and modernize key public institutions, the laws supporting them, and the personnel staffing them, thereby helping sustain the overall economic and social reform program which the government had initiated. This Note summarizes its impact on the ground and the lessons learned.